The Blair Witch Project [videorecording (Blu-Ray)] - Cora, Antonio (Lionsgate Entertainment, 2020)
Daniel Myrick and Eduardo Sanchez direct and script this mock documentary/horror film about a crew of student filmmakers who venture into Maryland's Black Hills Forest to document a local legend, the Blair Witch. They mysteriously disappear.